2018
DOI: 10.1002/cav.1812
|View full text |Cite
|
Sign up to set email alerts
|

Effects of interface on procedural skill transfer in virtual training: Lifeboat launching operation study

Abstract: A comparative study assessing the effect of interface type on procedural skill transfer during virtual training is presented. The aim of this research is to evaluate the transferability of two aspects of procedural skills, that is, procedural knowledge and technical skills. We established one group with a lecture and three virtual training groups with a combination of output and input devices: a monitor and keyboard/mouse, a head-mounted display (HMD) and joypad, and an HMD and wearable sensors. The task for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Further, previous research has revealed that simulation using HMDs improves knowledge transfer to solve real tasks (Falloon, 2020; Ganier, Hoareau, & Tisseau, 2014). Some studies (Civelek, Ucar, Ustunel, & Aydin, 2014; Jung & Ahn, 2018) have also combined haptic interfaces, such as wearable sensors, with an HMD to offer an embodied learning experience and improve manipulation abilities during simulation. Third, the integration of serious games with HMD settings can offer role‐play opportunities in more vivid scenarios to facilitate a higher degree of engagement and create more “realistic feelings” such as empathy or the sense of a professional identity (Feng, González, Amor, Lovreglio, & Cabrera‐Guerrero, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further, previous research has revealed that simulation using HMDs improves knowledge transfer to solve real tasks (Falloon, 2020; Ganier, Hoareau, & Tisseau, 2014). Some studies (Civelek, Ucar, Ustunel, & Aydin, 2014; Jung & Ahn, 2018) have also combined haptic interfaces, such as wearable sensors, with an HMD to offer an embodied learning experience and improve manipulation abilities during simulation. Third, the integration of serious games with HMD settings can offer role‐play opportunities in more vivid scenarios to facilitate a higher degree of engagement and create more “realistic feelings” such as empathy or the sense of a professional identity (Feng, González, Amor, Lovreglio, & Cabrera‐Guerrero, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies have been conducted to evaluate the influence of VR on training outcomes, and empirical reports have showed heterogeneous results (Dubovi et al, 2017;Gonzalez-Franco et al, 2017;Makowski et al, 2017;Jung and Ahn, 2018;Makransky et al, 2019). Logishetty et al (2019) found that surgeons trained using VR were more accurate in performing a total hip arthroplasty procedure compared to those that had undertaken the standard training.…”
Section: Vr Technology In Trainingmentioning
confidence: 99%
“…Moreover, previous studies have primarily tested the ability to remember and report procedures learned in VR, rather than objectively testing if the learned information was useful to improve task performance in a real setting (e.g., Dubovi et al, 2017;Makowski et al, 2017;Jung and Ahn, 2018). The sense of presence during a VR experience has been linked to better learning, but on the other hand, also to a higher cognitive load for the users (that may reduce the allocation of cognitive resources to learning, see Makransky et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Waller et al demonstrated that the effectiveness of learning in IVEs is similar to that of real world training with long exposure [ 39 ]. Recently, the use of IVEs has expanded to the learning of motor skills [ 8 ], motor rehabilitation [ 14 ], and professional skills [ 17 ]. Jung and Ahn described the attractiveness of virtual training to various industries because of its explicit cost-effectiveness and enhanced, safety considerations [ 17 ].…”
Section: Related Workmentioning
confidence: 99%
“…Recently, the use of IVEs has expanded to the learning of motor skills [ 8 ], motor rehabilitation [ 14 ], and professional skills [ 17 ]. Jung and Ahn described the attractiveness of virtual training to various industries because of its explicit cost-effectiveness and enhanced, safety considerations [ 17 ]. Although the higher fidelity of IVEs is expected to accelerate positive aspects of experiences in the virtual world, Mania et al reported that the environment with lower fidelity (flat shaded) paradoxically helped the participants to be more aware of the visual identity of the recognized object based on mental images [ 24 ].…”
Section: Related Workmentioning
confidence: 99%